2011
DOI: 10.1128/jb.01656-09
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Activation ofBacillus anthracisToxin Gene Expression and Virulence Requires the Carbon Catabolite Protein CcpA

Abstract: Sensing environmental conditions is an essential aspect of bacterial physiology and virulence. In Bacillus anthracis, the causative agent of anthrax, transcription of the two major virulence factors, toxin and capsule, is triggered by bicarbonate, a major compound in the mammalian body. Here it is shown that glucose is an additional signaling molecule recognized by B. anthracis for toxin synthesis. The presence of glucose increased the expression of the protective antigen toxin component-encoding gene (pagA) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 79 publications
0
54
0
Order By: Relevance
“…In agreement with the significance of AtxA in pathogenesis, atxA transcript levels are 5-to 6-fold greater in cultures grown at 37°C than in cultures incubated at 30°C (10). In the presence of glucose, the catabolite control protein CcpA stimulates transcription of atxA indirectly by an unknown mechanism (9). The redox state of the cell also appears to control atxA transcription.…”
mentioning
confidence: 99%
“…In agreement with the significance of AtxA in pathogenesis, atxA transcript levels are 5-to 6-fold greater in cultures grown at 37°C than in cultures incubated at 30°C (10). In the presence of glucose, the catabolite control protein CcpA stimulates transcription of atxA indirectly by an unknown mechanism (9). The redox state of the cell also appears to control atxA transcription.…”
mentioning
confidence: 99%
“…The CcpA⅐Hpr-Ser(P)-46 complex has an increased affinity for particular cis-acting sequences, termed catabolite-responsive element (cre) sequences, and thereby represses or enhances gene expression depending on the position of the cre in relation to the operator sequence (3,4). In a number of Gram-positive pathogens such as Bacillus anthracis (5), Clostridium difficile (6), Staphylococcus aureus (7), Staphylococcus epidermidis (8), Streptococcus pneumoniae (9), and Streptococcus pyogenes (10), CcpA is also involved in the regulation of virulence determinants.…”
mentioning
confidence: 99%
“…The corresponding amplified product was then digested with NheI and BamHI and ligated into the pETPhos plasmid, thus generating pETPhos_ccpA Ba , which was transformed and overexpressed, and the His-tagged CcpA was purified as described above. The B. anthracis ccpA recombinant vector was a kind gift from Marta Perego and purified as described by Chiang et al (5) to generate CcpA Ba .…”
mentioning
confidence: 99%
“…It has been shown that induction of Bacillus anthracis toxin gene expression by glucose and determined that CcpA transcription factor plays a positive role by indirectly regulating the transcription of the gene encoding AtxA. 31 Bacillus anthracis cultured on agar with 7% NaCl showed good growth (Figure 1 (F1)). We suspect, the nature of which is caused by the structure of the cell membrane that are typical of Bacillus anthracis.…”
Section: Discussionmentioning
confidence: 99%
“…Further also been shown that glucose is an additional signaling molecule recognized by Bacillus anthracis for toxin synthesis. 31 Bacillus anthracis cultured in nutrient broth when shaken showed the typical image that is like tendrils of silkworms (Figure 1 (C1)), while Bacillus cereus ( Figure 1 (C2)) and Bacillus thuringiensis (Figure 1 (C3)) remain murky. The fact is the hallmark of Bacillus anthracis.…”
Section: Discussionmentioning
confidence: 99%